Modulation of ASC-derived extracellular vesicles containing cargo that specifically enhances wound healing - Gurney, Jodi P.; Ludlow, John W.; Van Kanegan, Michael J.; Smith, Robin L. (Frontiers in Pharmacology, 2025)
IntroductionWe have developed a bioreactor-based production system for manufacturing Human Adipose Stromal Cell (ASC) extracellular vesicles (EVs), which includes exosomes, using a highly controlled and tunable environment that can modify the cargo of these nanovesicles. The patented innovation focuses on engineering novel pro-healing EVs with therapeutic activity and using a topical formulation to treat diabetic ulcers.MethodsTo evaluate biological activity of tuned ASC EVs, functional activity assays were performed using human primary dermal fibroblast and keratinocyte culture models. Molecular and biochemical assays were used to assess cytokine regulation, collagen production and cell migration. Rodent wound healing models were used to assess therapeutic potential of modified exosomes. A Human volunteer case study was carried out with a consenting individual suffering from chronic diabetic ulcers.ResultsHerein we demonstrate that our proprietary engineered ASC EVs, eXo3 exosomes, contain a unique activity profile that reduces inflammatory cytokines, stimulates collagen production, as well as activates keratinocyte and fibroblast proliferation and migration. When formulated with an emollient and topically applied to an in vivo excisional wound model, tuned eXo3 exosomes demonstrated enhanced wound closure, increased keratinization, collagen deposition, and overall improved recover rate. In a clinical case study addressing non-healing diabetic foot ulcers, conducted under informed consent, topical treatment with tuned eXo3 exosomes formulated in a proprietary gel serum showed complete wound closure and dermal regeneration.ConclusionOur current research efforts have developed an EV manufacturing system that can be directed to improve the healing capacity of ASC-derived EVs. We show enhanced wound healing and repair activity in vitro and in vivo. Our data supports the regenerative properties of exosomes and reinforces their strong therapeutic potential.